Pembelajaran PJOK Materi Bela Diri SMA Kelas 10 di Kecamatan Sukorejo Kabupaten Kendal - Negara, Muhammad Shidiq Satria; Setiawan, Ipang (Universitas Negeri Semarang, 2023)
The purpose of this study was to identify and describe learning planning, implementation of learning, and evaluation of self-defense learning. This type of research is descriptive research with a quantitative approach. The sampling technique was purposive sampling technique. Data collection techniques using a questionnaire. The data analysis technique used descriptive technique. Based on the results of research, the implementation of Physical Education, Sports and Health (PJOK) learning in general has not been able to take place well. It can be seen from the results of research on three important aspects of learning, namely learning planning, where the results of student assessments are 76.81% included in the Good category, and the results of teacher assessments 62.5% are included in the Good category. in the Less Good category and the results of the teacher's assessment of 58.5% are included in the Less Good category. Learning evaluation where the results of student assessments 71.17% are included in the Good category and the results of teacher assessments are 50% included in the Less Good category. Overall less than optimal. The thing that needs to be considered is that subject teachers can better utilize learning media to support the process of teaching and learning activities so that the results achieved can be maximized.